2019
DOI: 10.1039/c8re00304a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient liquid-phase hydrogenolysis of a lignin model compound (benzyl phenyl ether) using a Ni/carbon catalyst

Abstract: Efficient liquid-phase hydrogenolysis of benzyl phenyl ether using Ni/CB in an EtOH/H2O co-solvent system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…For example, acid or base is usually added for promoting hydrolysis reaction, metal oxide catalysts are employed to improve the oxidative reactions, and many transition metal‐based catalysts (Ni, Pd, Ru, Pt, etc.) are found to have higher reactivity for hydro‐deoxygenation (HDO), hydrogenolysis, and hydrogenation reactions . These reactions happen simultaneously in the same system which creates difficulty in controlling the lignin fractionation to selective production of target compounds.…”
Section: Introductionmentioning
confidence: 99%
“…For example, acid or base is usually added for promoting hydrolysis reaction, metal oxide catalysts are employed to improve the oxidative reactions, and many transition metal‐based catalysts (Ni, Pd, Ru, Pt, etc.) are found to have higher reactivity for hydro‐deoxygenation (HDO), hydrogenolysis, and hydrogenation reactions . These reactions happen simultaneously in the same system which creates difficulty in controlling the lignin fractionation to selective production of target compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Reductive depolymerization of lignin involves the hydrogenolysis of C–O and C–C interunit linkages, which is usually occurred in the presence of a catalyst under hydrogen pressure [ 187 ]. The main product of the reaction is a bio-oil rich in substituted guaicyl and syringyl type compounds as well as alkylated phenols [ 182 ].…”
Section: Lignin Hydrogenolysis To Valuable Phenolic Compoundsmentioning
confidence: 99%
“…Additionally, metal-catalyzed oxidative lignin depolymerization has offered great advantages because of its high selectivity and relatively milder reaction condition; therefore, metal supported catalysts have been extensively used for lignin valorization [13,28,29]. It has been reported that Au/TiO 2 , however, favored ring-opening reactions of lignin while Pt/TiO 2 effectively promoted lignin condensation and gave minimal effect on ringopening reaction [30].…”
Section: Introductionmentioning
confidence: 99%